Studi Fenomenologi: Pengalaman Perawat Dalam Menangani Pasien Dengan Covid-19 di Rumah Sakit Di Jakarta Tahun 2020 - Opan Sukiman; Agung Waluyo; Diana Irawati (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Deaths from COVID-19 continue to increase globally, the diversity of management strategies during the pandemic has resulted in high rates of local transmission. Indonesia is currently in the early stages of the COVID-19 pandemic, where thw situation of the spread of COVID-19 has almost reached all regions in Indonesia’s provinces with the number of cases and/or the number of deaths increasing. Health care providers, particularly nurses, experience not only increased workloads but also psychological changes associated with the anxiety and fear that nurses are forced to face. This qualitative study explored of nurses caring for COVID-19 patient. This study used a phenomenological approach with 6 male an 4 female participants. The interviews were conducted by telephone and were analysed by thematic analysis methodes. There are four themes identified in this study, including changes that have been felt since treating COVID-19 patients, behavior in dealing with perceived changes, obstacles faced while in service and expectations during COVID-19 patients. Comprehensive support and intensive training are needed by nurses and provide an adequate basis in providing optimal nursing care for patients. Comprehensive support both morally and materially as well as intensive traineng such as pre-employment training, adaptation training for other patient nurses in the infection department and negative pressure ward training are needed by nurses for the welfare of nurses and as an adequate basis in providing optimal nursing care for patients. Keywords: coronavirus disease 2019; nurses; change experienced by nurses caring for COVID-19 patient ABSTRAK Kematian akibat COVID-19 terus meningkat secara global, keberagaman strategi penatalaksanan selama pandemik menyebabkan tingginya angka penularan secara lokal. Indonesia saat ini berada pada tahap awal pandemi COVID-19, dimana situasi penyebaran COVID-19 yang sudah hampir menjangkau seluruh wilayah di Provinsi di Indonesia dengan jumlah kasus dan/atau jumlah kematian semakin meningkat. Penyedia layanan kesehatan, khususnya perawat tidak hanya mengalami peningkatan beban kerja tetapi juga perubahan psikologis yang berhubungan dengan kecemasan dan ketakutan yang dimana perawat dipaksa untuk menghadapi situasi tersebut. Tujuan penelitian ini adalah untuk menggali pengalaman perawat dalam menangani pasien dengan COVID-19. Studi ini menggunakan pendekatan fenomenologi dengan jumlah partisipan 6 laki-laki dan 4 perempuan. Wawancara dilakukan melalui telepon dan dianalisis dengan metode analisis tematik. Terdapat 4 tema yang diperoleh dalam penelitian ini yaitu perubahan yang dirasakan sejak menangani pasien dengan COVID-19, perilaku mengatasi perubahan yang dirasakan, kendala yang ditemui saat berdinas serta harapan selama menangani pasien dengan COVID-19. Dukungan menyeluruh baik secara moril maupun materil serta pelatihan intensif seperti pelatihan pra kerja, pelatihan adaptasi perawat pasien lain di departemen infeksi serta pelatihan bangsal tekanan negatif diperlukan perawat demi kesejahteraan perawat dan sebagai dasar yang cukup dalam memberikan asuhan keperawatan yang optimal bagi pasien. Kata kunci: COVID-19; perawat; perubahan perawat dalam menangani pasien dengan COVID-19